The Struggle for Freedom as Illustrated in Mark Twain’s The Adventure of Huckleberry Finn in Relation to Social Welfare - Mutmainnah Magfirah (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
This study aims to describe the struggles experienced by the two main characters in the novel in getting their freedom and also to elaborate the important of freedom for the main characters as human rights. The research method used was a qualitative descriptive method with the sociology of literature approach. The primary data were collected from descriptions and utterances of the main characters and narrators in the novel. The supporting data were obtained from the library, internet, journals, and articles. The results of this research indicate that there is struggle of the main characters in obtaining their freedom as a human in this novel. Huckleberry Finn as the main character fought for his freedom from a drunk and abusive father, while Jim, as the second main character fought for his freedom from slavery. The two figures then met and made an adventure together to get their own freedom.